Variations in morphology, phenology and essential oil composition of sweet basil (Ocimum basilicum L.) germplasm accessions - A Srivastava, A A Naqvi, SPS Khanuja, Ajay Pratap Singh, Samresh Dwivedi, S Bharati, M Singh, V Singh (Journal of Spices and Aromatic Crops, 2002)
Morphology, phenology and essential oil composition variations were analysed in germplasm accessions of sweet basil (Ocimum basilicum L.), an important medicinal and aromatic crop. Significant variations were observed for morphological and essential oil traits. All the fourteen accession studied could be characterised as ten morphotypes ObC-A through ObC-J. Chemotypic indexing resulted in assigning three chemotypes namely, linalool, methyl chavicol and methyl cinnamate types on the basis of major oil component. Linalool chemotype could also be subgrouped into four subtypes as significant differences were observed in minor components too. Three phenological types were also defined based on genotype performance during different seasons.